Regional features of thunderstorm activity (on the example of the territory of the Kabardino-Balkarian Republic) - A. Kh. Adzhiev; A. A. Cherkesov; Z. M. Kerefova (Наука. Инновации. Технологии)
Introduction. Thunderstorm activity refers to one of the regional climatic characteristics of a limited area. Thunderstorms result in lightning discharges and an increase in the electric field strength of the surface layer of the atmosphere. Considered lightning discharges, which are divided into positive and negative. The number of thunderstorm days recorded on the territory of the KBR for the period from 2012 to 2022 was analyzed and calculated. It is shown that the relief and climate of the study area contribute to the heterogeneous development of thunderstorm processes.Materials and research methods. The lightning direction finding network of the Federal State Budgetary Institution "VGI" with spatially separated sensors LS8000 and LS7002 was used in the work. To determine the characteristics of thunderstorm activity, we used long-term data from the specified lightning direction finding network. The analysis of data from the LS8000 lightning direction finding system (GPS) confirms that ground-based lightning is unevenly distributed over the territory of the Kabardino-Balkarian Republic. For the analysis of thunderstorm activity, data over the period 2012 to 2022 were used. The following characteristics were studied the long-term course: the number of thunderstorm days in different months of the year; the total number of lightning of all types registered in the territory of the Kabardino-Balkarian Republic; number of lightnings of negative polarity; number of registered positive lightning; values (peak) of lightning currents in ground discharges; average air temperature for the warm period of the year.Research results and their discussion. During the studied period of time on the territory of the KBR, 869 days with a thunderstorm were recorded by the lightning registration system. A day was considered a thunderstorm if at least four lightning strikes were recorded per day. The largest number of days with 90 thunderstorms were noted in 2016 and 2018; the smallest number of days with thunderstorms was noted in 2022. This year, according to the data of Roshydromet, weather stations on the territory of the KBR, was marked as the driest year. The average annual number of days with thunderstorms in the considered time interval was 79 days, which is 19 more than recommended for lightning protection measures.Conclusions. The analysis performed showed a trend towards a decrease in thunderstorm activity on the territory of the Kabardino-Balkarian Republic, as well as the values of the number of lightning per year of negative polarity. Linear trend expressions for the indicated characteristics are obtained.